Do driver’s characteristics, system performance, perceived safety, and trust influence how drivers use partial automation? A structural equation modelling analysis - Nordhoff, Sina; Stapel, Jork; He, Xiaolin; Gentner, Alexandre; Happee, Riender (Frontiers in Psychology, 2023)
The present online survey investigated the impact of driver’s characteristics and system performance on perceived safety and trust, and the impact of perceived safety and trust in partially automated cars on use of partial automation by a structural equation modelling analysis. Respondents positively rated the performance of Adaptive Cruise Control (ACC) and Lane Keeping Assistance (LKA). ACC was rated higher than LKA and detection of lead vehicles and lane markings was rated higher than smooth control for ACC and LKA, respectively. Respondents reported to primarily disengage (i.e., turn off) partial automation due to a lack of trust in the system and when driving is fun. They rarely disengaged the system when they noticed they become bored or sleepy. The structural equation modelling analysis revealed that driver’s personality trait neuroticism did impact perceived safety but not trust in partially automated cars. Age did not significantly affect perceived safety and trust, but driver’s gender (males) and reported annual driving mileage was positively associated with perceived safety and trust in partially automated cars, respectively. We also found significant positive effects of the perceived system performance (ACC and LKA) on perceived safety and trust. Trust and perceived safety both had positive impacts on using partial automation for comfort and pleasure, with the influence of trust being almost twice as large as perceived safety. Drivers with high levels of trust were less likely to disengage the system when it was not necessary, or was distracting or confusing to use. Our study generates important knowledge about the relationships between driver’s characteristics, system performance, perceived safety, trust and automation use. Future research should re-assess the suitability of the short 10-item scale as measure of the Big-Five personality traits, and investigate the impact on perceived safety, trust, and automation use.